Nursing health assessment : a best practice approach - Jensen, Sharon, 1955- 4 0 16; 5 (Philadelphia, Pennsylvania : Wolters Kluwer/Lippincott Williams & Wilkins Health, 2011)
Nursing Health Assessment: A Best Practice Approach reflects a progressive and modern view of nursing practice. The text combines elements of traditional Health Assessment texts with innovative elements that facilitate understanding of how best to obtain accurate data from patients. It not only includes thorough and comprehensive examinations for each specific topic, but also presents strategies for adapting questions and techniques when communication is challenging, the patient's responses are unexpected, or the patient's condition changes over time. Unique features assist with application and analysis, enhancing critical thinking skills and better preparing all readers for active practice. A real-life approach is introduced at the beginning of each chapter and continued throughout. This includes recurring features that provide related questions, additional data, and variations that challenge one to modify responses. These cases encourage the progressive building and synthesis of knowledge. In addition to the case studies, other distinctive aspects of this text include the following: Emphasis on health promotion, risk-factor reduction, evidence-based critical thinking, and diagnostic reasoning. The end of the chapter demonstrates how to use critical thinking and diagnostic reasoning to cluster data and to analyze findings. End-of-chapter review sections contain questions and critical thinking challenges related to the previously established case study. Additionally, the last section of each chapter focuses on prioritizing and modifying assessment to promote the best care possible, and summarizing multiple findings to create appropriate plans for patient's health--Provided by publisher.
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; Nursing assessment.;Nursing Assessment. -- 20; 20; 2